Relationship between therapeutic changes in blood pressure and outcomes in acute stroke: a metaregression - Geeganage, Chamila; Bath, Philip M.W. (American Heart Association, 2009)
Both low and high blood pressure (BP) during the acute phase of stroke are associated independently with a poor outcome. Several small clinical trials have involved the alteration of BP and this study assessed the relationship between change in BP and functional outcome. Randomised controlled trials of interventions that would be expected, on pharmacological grounds, to alter BP in patients within one week of the onset of acute ischaemic or haemorrhagic stroke were sought using electronic searches. Data were collected on BP and clinical outcome. The relationship between the difference in on-treatment BP and odds ratios (OR) for outcomes was assessed using meta-regression. Thirty-seven trials involving 9,008 patients were included. A ‘U’ or ‘J’ shaped relationship were found between on-treatment BP difference and early death, death at the end of 90 day follow up, and combined death or dependency at the end of follow up. Although outcomes were not significantly reduced at any level of change in BP, the lowest odds occurred at: early death (OR 0.87, 95% confidence interval, CI 0.54 to 1.23) - 8.1 mmHg; death at end of follow up (OR 0.96, 95% CI 0.31 to 1.65) - 14.4 mmHg; and combined death or dependency at end of follow up (OR 0.95, 95% CI 0.11 to 1.72) - 14.6 mmHg. Although large falls or increases in BP are associated with a worse outcome, modest reductions may reduce death, and combined death or dependency, although the confidence intervals are wide and compatible with overall benefit or hazard.